Impact of Intense Social Media Usage on Sleeping Pattern - Ilham, Nadifah Adya; Mahisha Mutharrif Laila; Muhammad Aditia Syauqi; Mohammad Ardy Audya Armadhana; Anusua Ghosh (Association for Scientific Computing Electrical and Engineering, 2022)
The sleeping pattern refers to our habit of resting our bodies after a day's activities. This involves the number of hours spent sleeping and the overall wellbeing of the body when performing everyday tasks. When we don't get enough sleep, it immediately affects our health. This unhealthy sleep pattern is caused by several things, one of which is the intense usage of social media. The use of Social Media can affect health, both physically and psychologically. This research relies on systematic literatur review (SLR) method obtained from databases, namely Google Scholar from many countries in the world, and data about digital 2021 global overview report from Hootsuite & We Are Social. Of the 55 studies obtained, 41 studies stated that Insufficient sleep was found to be linked to social media use. daytime sleepiness, insomnia, or sleep patterns. According to the research, excessive usage of social media is related to sleep problems or disruptions. The usage of social media will have a beneficial impact, since it will make daily tasks easier. However, unrestricted use of social media can have a detrimental effect on sleep habits.